Umpolung of Enamines: An Overview on Strategies and Synthons - Sukhorukov, Alexey Yu. (Synlett, 2020)
Umpolung strategies are of considerable interest to organic chemists because they provide alternative synthetic routes to those imposed by the natural polarity of classical synthons. Reverse-polarity reactions of aldehydes, α,β-unsaturated carbonyl compounds, and imines are deeply embedded in the methodology of organic synthesis. In recent years, umpolung of enols and enamines has received much attention as a novel strategy to access α-substituted ketones. Here, state-of-the-art approaches to umpolung of enamine reactivity are discussed, with a particular focus on recent developments in this field from the author’s research group.1 Introduction2 Approaches toward Umpolung of Enamines3 Umpolung of Enamines through Single-Electron Oxidation4 Azadienes as Synthetic Equivalents of Enamine Umpolung Synthons5 Enamines Possessing a Leaving Group at the Nitrogen Atom6 Enamines Possessing a Directing Group at the Nitrogen Atom7 Summary and Outlook
Keywords: umpolung; enamines; ketones; nitro compounds; imines